Pengaruh Kualitas Produk, Promosi, dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Studi pada Dealer Motor Honda PT. Tirto Agung Porong - Moh. Bachrul Rizki; Rizky Eka Febriansah; Alshaf Pebrianggara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to analyze the influence of product quality, brand image, and price perception on the consumer decision-making process for purchasing Honda motorcycles. The population of this study consists of all residents of Sidoarjo. The sample was determined using the Lameshow formula, resulting in a sample size of 96.04, which was rounded up to 100 respondents. This study employed a non-probability sampling technique, specifically accidental sampling. The variables studied include product quality, promotion, and brand image. The t-test results show that product quality has a positive and significant effect on motorcycle purchasing decisions, promotion has a positive and significant effect on motorcycle purchasing decisions, and brand image also has a positive and significant effect on motorcycle purchasing decisions at the Tirto Agung Porong Dealership.